(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to describe the improvement of students’ writing skills using the Numbered Head Together (NHT) Cooperative Type model in Indonesian language learning in class IV SDN 01 Asam Kumbang. This research is a Classroom Action Research (CAR) using qualitative and quantitative approaches carried out in two cycles. Each cycle consists of planning, implementation, observation and reflection. The subjects in this study were teachers and grade IV students of SDN 01 Asam Kumbang, totaling 19 people in the January-June semester of the 2024/2025 school year. The research data are in the form of observations of teaching modules, observations of teacher and learner activities, and the results of students’ writing skills using the Numbered Head Together (NHT) Cooperative Type model. Data collection techniques in the form of observation analysis or observation, tests and non-tests. The results of observations of teaching module planning cycle I 85.42% (B), increased in cycle II 91.66% (SB). The results of observations of the teacher aspect of cycle I 83.33% (B), increased in cycle II 95.83% (SB). The results of the observation of the learner aspect of cycle I 83.33% (B), increased in cycle II 95.83% (SB). The writing skills of students in cycle I 70.45 (C), increased in cycle II 86.08% (B). The research shows that the Numbered Head Together (NHT) Cooperative model can improve the writing skills of students in learning Indonesian in class IV of SDN 01 Asam Kumbang.